The Architecture of Sunan Bonang's Tomb: Commodification of Sacred Zones in Religious Tourism - Ghozi, Ahmad; Purwasito, Andrik; Warto, Warto; Rais, Wakit Abdullah (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2025)
The significant number of visitors visiting the Sunan Bonang Tomb in Indonesia is believed to contribute to the commodification of sacred zones for religious tourism at the tomb. This study focused on exploring how sacred zones are transformed into religious tourism destinations at the Sunan Bonang tomb in Tuban, Indonesia. Qualitative research involved gathering field data through participant observation, in-depth interviews, and documentation studies. Researchers conducted data triangulation to confirm the accuracy of the gathered data. The research results were examined using Foucault's perspectives through archaeological and genealogical approaches. This study identified key factors contributing to the commodification of Sunan Bonang's tomb for religious tourism, including: 1) the established religious tradition within Islamic communities that influence the occurrence of commodification, 2) government support aimed at enhancing the attraction of cultural products for religious tourism, and 3) the role of the foundation as the holder of management authority managing the commodification of Sunan Bonang's tomb for religious tourism. Commodification focuses more on creating sacred zones at the Sunan Bonang’s Tomb.